CircCA12 Promotes Malignant Process via Sponging miR-1184 and Upregulating RAS Family in Bladder Cancer - Jiang, Lijuan; Wang, Yanjun; Tang, Huancheng; Li, Xiangdong; Huang, Chaowen; Liu, Zhuowei; Zhou, Fangjian; Wang, Xiaolan; Li, Yonghong (Frontiers in Genetics, 2021)
Circular RNAs (circRNAs) refer to a panel of non-coding RNAs that serve as a pivotal mediator in regulating gene expression and pathological responses. However, the potential function and expression profile of circRNAs in bladder cancer remain unknown. In the research, we investigated the role of circCA12 in the development of bladder cancer. We found circCA12 was significantly upregulated in bladder cancer cell lines and tissues by qRT-PCR analysis. CCK-8, colony formation and xenograft assays ware employed to explore the effect of circCA12 exert on bladder cancer. As a result, knockdown of circCA12 suppressed the proliferation and colony-formation capability of bladder cancer cells. After transfected by si-cirCA12 or sh-circCA12, migration and metastasis ability of bladder cancer cells were significantly abated, both in vitro and in vivo assays. Based on the luciferase reporter and RIP assays, we found circCA12 binds to miRNA-1184 as a miRNA sponge and by which, up-regulates the expression of RAS family (NRAS, KRAS, HRAS). In conclusion, cicrCA12/miRNA-1184/RAS family was identified as a regulatory axis in bladder cancer progression.